2013
DOI: 10.1111/papt.12002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to individual and group cognitive behaviour therapy of social phobia

Abstract: Anticipatory worry appears to be a particularly important trait for explaining variance in the outcome of social phobia. The finding is consistent with the assumed stability of such personality traits over time. Further studies are warranted to replicate the finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
(64 reference statements)
1
6
0
1
Order By: Relevance
“…These results are consistent with previous research. Self-directedness has been found to have a favorable effect on the CBT treatment outcome in social phobia [67] and during follow-up in eating disorders [68]. It should be noted that this relationship has not been confirmed for group therapy.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with previous research. Self-directedness has been found to have a favorable effect on the CBT treatment outcome in social phobia [67] and during follow-up in eating disorders [68]. It should be noted that this relationship has not been confirmed for group therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the Brunnsviken Brief Quality of life scale (BBQ) (Lindner et al, 2016) was used to measure subjective quality of life. Established Swedish versions of all scales were used (Hedman et al, 2010;Johansson et al, 2013;Mörtberg & Andersson, 2013).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…For example, higher pre-treatment rumination is associated with poorer treatment response for major depressive disorder and dysthymia (Ciesla & Roberts, 2002;Schmaling, Dimidjian, Katon, & Sullivan, 2002). Similarly, worry has been shown to predict poorer treatment response at post-treatment and 1-year follow up in individual and group cognitive behavior therapy (CBT) for social anxiety disorder (M€ ortberg & Andersson, 2014). Others have found that rumination is associated with delayed symptom remission in mild-moderately depressed participants (Jones, Siegle, & Thase, 2008) and greater likelihood of relapse following mindfulness based cognitive behavior therapy (Michalak, H€ olz, & Teismann, 2011).…”
mentioning
confidence: 98%